Effect of Lactobacillus plantarum C014 on Innate Immune Response and Disease Resistance against Aeromonas hydrophila in Hybrid Catfish. (21st December 2013) - Butprom, Sureerat; Phumkhachorn, Parichat; Rattanachaikunsopon, Pongsak
Abstract : A bacterial strain isolated from intestines of hybrid catfish ( Clarias gariepinus Male × Clarias macrocephalus Female) exhibited an in vitro inhibitory effect on a fish pathogen, Aeromonas hydrophila TISTR 1321. By using the 16S rDNA sequence analysis, it was identified as Lactobacillus plantarum C014. To examine whether L. plantarum C014 had potential for use as an immunostimulant and biocontrol agent in hybrid catfish, the fish diet supplemented with L. plantarum C014 (10 7  CFU/g diet) was prepared and used for the in vivo investigation of its effect on innate immune response and disease resistance of hybrid catfish. Two innate immune response parameters, phagocytic activity of blood leukocytes and plasma lysozyme activity, were significantly enhanced in the treated fish after 45 days of feeding. Feeding the fish with the L. plantarum C014 supplemented diet for 45 days before challenging them with A. hydrophila at the dose of L D 50 could reduce the mortality rate of the fish from 50% (in control group) to 0% (in treated group). Based on its origin and beneficial effect on innate immune response and disease resistance, L. plantarum C014 may be a potential candidate for use as a natural and safe immunostimulant and biocontrol agent in hybrid catfish.